University Course Scheduling using the Evolutionary Algorithm - Ade Jamal (Universitas Al Azhar Indonesia, 2011)
Course scheduling problem is hard and time-consuming to solve which is commonly faced by academic administrator at least two times every year. This problem can be solved using search and optimization technique with many constraints. This problem has been well studied in the past, and still becomes favorite subject for researchers. We will briefly discuss the convergence difficulty in our initial work on this subject using a modified hill-climbing search technique[8]. In this paper, an evolutionary algorithm is applied to solve the course scheduling problem and studying mutation techniques involved in the algorithm.